Electronic Educational Resource as a Source and Means of Developing Digital Education - Magomed Abdurazakov; Tatiana Litvinova; Georgy Tokmazov; Nadezhda Salangina (Современные информационные технологии и IT-образование)
The article examines digitalization as one of the main and noticeable phenomena of society and its impact on the content, form, and means of education. It is concluded that educational information and knowledge receive digital expression in an electronic educational resource (EER), which is at the same time a form, a means, and the content of education. Such a sequence of states, expressions and presentations of educational information in the electronic digital sphere requires a certain analysis and comprehension in terms of its significance, qualitative and quantitative impact on education and learning outcomes, personal development and self-development. The basic information of the EER is a reflection of the goals of education and specific subject-based educational training in accordance with its purpose and constitutes their content (education and subject-based training). Moreover, the purpose of educational information and electronic educational resources is the formation and development of relevant subject, interdisciplinary and general educational competencies, which is a condition for the creation and subsequent functioning of electronic educational resources as a standard educational tool that meets the requirements of the Federal State Educational Standard (FSES). It is concluded that e-learning is based on the digital representation of information and information technology. Digital methods of presenting and displaying information have sufficient capabilities for this. However, a certain differentiation is necessary here, taking into account the specific audience, that is, educational information must meet the relevant requirements: be accurate and reliable; accessible to students, taking into account their age categories and psychological characteristics; be colorfully designed with color highlighting texts of varying importance and a structured display of the source of its perception; have the ability to display graphically; have sound and/or musical accompaniment; have hyper-navigation tools and interactive menus. It is concluded that e-learning is based on the digital representation of information and information technology. Digital methods of presenting and displaying information have sufficient capabilities for this. However, a certain differentiation is necessary here, taking into account the specific audience, that is, educational information must meet the relevant requirements: be accurate and reliable; accessible to students, taking into account their age categories and psychological characteristics; be colorfully designed with color highlighting texts of varying importance and a structured display of the source of its perception; have the ability to display graphically; have sound and/or musical accompaniment; have hyper-navigation tools and interactive menus. It is noted that e-learning requires the creation and use of an electronic educational resource in educational and cognitive activities through interaction with the information and educational environment. In modern teaching, the “monologue” of the teacher (teacher) with students is becoming less effective. The subject of education must learn to carry out his educational and cognitive activities in the appropriate IEE and there cannot and should not be antagonistic contradictions in his relationship with the environment.